Odpowiedzi

Najlepsza Odpowiedź!
2009-12-07T22:28:07+01:00
A)
(x+7)(x-3)-(x-1)(x+5) = x² + 7x - 3x - 21 - (x² - x + 5x - 5) = x² + 7x - 3x - 21 - x² + x - 5x + 5 = -16

b)
x⁴-(x²-2y)(x²+2y) = x⁴-(x⁴- 2x²y + 2x²y - 4y²) = x⁴- x⁴+ 2x²y - 2x²y + 4y² = 4y²
1 4 1
2009-12-07T22:30:14+01:00
Odpowiedz do A:
(x+7)(x-3)-(x-1)(x+5)
= x² + 7x - 3x - 21 - (x² - x + 5x - 5)
= x² + 7x - 3x - 21 - x² + x - 5x + 5
= -16
odpowiedz do B:
x⁴-(x²-2y)(x²+2y)
= x⁴-(x⁴- 2x²y + 2x²y - 4y²)
= x⁴- x⁴+ 2x²y - 2x²y + 4y²
= 4y²
2009-12-08T00:39:13+01:00
A) (x+7)(x-3)-(x-1)(x+5) = x² + 7x - 3x - 21 - (x² - x + 5x - 5) = x² + 7x - 3x - 21 - x² + x - 5x + 5 = -16 b) x⁴-(x²-2y)(x²+2y) = x⁴-(x⁴- 2x²y + 2x²y - 4y²) = x⁴- x⁴+ 2x²y - 2x²y + 4y² = 4y² powinno być ok;p